2021
DOI: 10.21203/rs.3.rs-1089201/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Codon-specific Ramachandran plots show amino acid backbone conformation depends on identity of the translated codon.

Abstract: Synonymous codons translate into chemically identical amino acids. Once considered inconsequential to the formation of the protein product, there is now significant evidence to suggest that codon usage affects co-translational protein folding and the final structure of the expressed protein. Here we develop a method for computing and comparing codon-specific Ramachandran plots and demonstrate that the backbone dihedral angle distributions of some synonymous codons are distinguishable with statistical signific… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(33 citation statements)
references
References 46 publications
(47 reference statements)
3
28
2
Order By: Relevance
“…The p-value distributions presented in Figure 2 indicate that significant differences between codonspecific Ramachandran plots are found for a substantial number of tested hypotheses: 78% for H, 87% for E and and 92% for Others. The results for α-helical structures strongly differ from those presented in [1], where no significant difference was retrieved (see Figure 4 in the original study). In addition, the proportion of significant differences for E is also considerably higher than in [1], where only 39% of the synonymous pairs were identified as structurally distinct.…”
Section: Goodness-of-fit Between Codon-specific (ϕ ψ) Distributionscontrasting
confidence: 81%
See 2 more Smart Citations
“…The p-value distributions presented in Figure 2 indicate that significant differences between codonspecific Ramachandran plots are found for a substantial number of tested hypotheses: 78% for H, 87% for E and and 92% for Others. The results for α-helical structures strongly differ from those presented in [1], where no significant difference was retrieved (see Figure 4 in the original study). In addition, the proportion of significant differences for E is also considerably higher than in [1], where only 39% of the synonymous pairs were identified as structurally distinct.…”
Section: Goodness-of-fit Between Codon-specific (ϕ ψ) Distributionscontrasting
confidence: 81%
“…On the other hand, it requires a substantial reduction of sample sizes, which may imply an important loss of information in some cases and thus a substantial power reduction. Indeed, the maximum sample size in [1] is set to N max = 200, whereas, for instance, the median sample size for α-helical conformations is 1414 and only 1.16% of the samples have sizes below N max .…”
Section: Goodness-of-fit Between Codon-specific (ϕ ψ) Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this 64-codon alphabet is highly degenerate, with most amino acids being encoded by up to six different codons, current research suggests that codons encoding the same amino acid ( synonymous ) are not used interchangeably. Synonymous codon usage has been correlated with protein structural features [27, 28], and nearly 60 synonymous mutations have been linked to human disease [29]. A recent experiment suggested that most synonymous mutations in yeast are strongly deleterious [30], although these results have since been contested [31, 32].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that some proteins may fold into native structures that are more kinetically accessible than conformations of the lowest free energy [86]. Indeed, experimental observations have been reported that synonymous codon substitutions result in conformational changes in the translated proteins, due to kinetic changes in the co-translational folding of the nascent chain on the ribosome [8790]. These results are consistent with the idea that the native structures of some proteins may be determined by kinetics rather than thermodynamics.…”
Section: Discussionmentioning
confidence: 99%